Applying evidence-based judicial review to assess the constitutionality of the law requiring HIV-testing before surgical and dental procedures: The case of the Botswana Public Health Act 2013 - Nienaber, A.G. (Annelize Gertruida) (University of Pretoria, 2019)
Mini Dissertation (LLM)--University of Pretoria, 2018.